2010
DOI: 10.1002/pssa.201026400
|View full text |Cite
|
Sign up to set email alerts
|

Effects of post‐growth annealing on physical properties of SrRuO3 thin film grown by MOCVD

Abstract: 6392 3003We report on the annealing effects on strontium ruthenate thin films deposited on SrTiO 3 using liquid-delivery metalorganic chemical vapor deposition (MOCVD). The results of high resolution X-ray diffraction (HR-XRD), Raman spectroscopy, atomic force microscopy (AFM), and electrical resistivity, before and after a post-growth annealing process were analyzed and compared. XRD and Raman spectroscopy for the asdeposited film revealed that the film had c-axis orientation and contained RuO 2 as secondary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 33 publications
2
5
0
Order By: Relevance
“…The reduced resistivity value for sample 2 is caused by the existence of the RuO 2 (bulk RuO 2 has a resistivity of = 35 cm [26]) and Ru ( = 12 cm [27]) impurity phases. This is in agreement with our recent observation that the anneal-related loss of the RuO 2 impurity phase leaves a stoichiometric SrRuO 3 layer of higher resistivity [15]. This observation is also consistent with the results of Lee and Tsai [14], who found that the sheet resistivity of SRO thin films decreases with the increase of the ruthenium content by changing the chemical ratio of Ru/(Sr + Ru) and, finally, the Curie transition kink even vanishes.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The reduced resistivity value for sample 2 is caused by the existence of the RuO 2 (bulk RuO 2 has a resistivity of = 35 cm [26]) and Ru ( = 12 cm [27]) impurity phases. This is in agreement with our recent observation that the anneal-related loss of the RuO 2 impurity phase leaves a stoichiometric SrRuO 3 layer of higher resistivity [15]. This observation is also consistent with the results of Lee and Tsai [14], who found that the sheet resistivity of SRO thin films decreases with the increase of the ruthenium content by changing the chemical ratio of Ru/(Sr + Ru) and, finally, the Curie transition kink even vanishes.…”
Section: Resultssupporting
confidence: 92%
“…The reduction of the vertical lattice parameter for sample 3 is caused by partial plastic relaxation of the layer due to defects which are induced by the incorporation of the extra phase Sr 3 Ru 2 O 7 and the low O 2 supply during deposition. On the other hand, the slight increase of the lattice parameter of sample 3 in comparison with sample 2 could be caused by Ru-deficiency, as observed recently [15]. Dabrowski et al [18] also reported that Ru vacancies decrease the average interatomic Ru-O distance and rotation of the RuO 6 octahedra as Sr atoms relax towards the Ru vacancy increases the unit cell volume.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…While Raman scattering has been employed to investigate the phase transformation and soft modes in the bulk BiFeO 3 , Raman spectra from (BiPb)FeO 3 layers are in general difficult to obtain since an underlying perovskite SrRuO 3 /SrTiO 3 structure overwhelms the scattering signal emanating from the top (BiPb)FeO 3 layers. By subtracting the contributions arising solely from the SrRuO 3 /SrTiO 3 structure, it is possible to obtain the contribution of the (BiPb)FeO 3 layer in the Raman signal 17 . Figure 1a shows one of the representative Raman spectra of the (BiPb)FeO 3 /SrRuO 3 /SrTiO 3 heterostructure grown at T g  = 650 °C ( x ) as well as the base SrRuO 3 /SrTiO 3 ( y ) structure.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, both fitting MDC dispersion and analysis of real and the imaginary part of the self-energy consistently points towards the existence of a kink around -44 meV. Remarkably, the position of this kink is comparable to the energy of the B 2g phonon mode (354 cm −1 = 43.9 meV) that corresponds to the motion of apical oxygen ions 41 . Meanwhile, in (001) SRO films, the kink is attributed to the coupling between electron and in-plane oxygen vibration-driven A g (540 cm −1 = 67 meV) mode 23 .…”
mentioning
confidence: 60%